GCSE mathematics - "Powell, Robert" (BPP ( Letts Educational ) Ltd London, 1993)
A mathematics text which is one of a series covering the Key Stage 4/GCSE Programmes of Study and Attainment Targets set out by all the major examining bodies. Features include guidance on studying, revising, coursework and types of assessment question; exercises and projects; and exam questions.